ANALYSIS OF THE DEVELOPMENT STRATEGY OF UMKM FASHION HALAL LANGGAM BATIK BASED ON SUSTAINABILITY - Fitri, Syahruna; Marliyah, Marliyah; Inayah, Nurul (LPPM Universitas Trunojoyo Madura, 2025)
The success of MSMEs in developing the sustainability-based halal fashion sector will largely depend on the implementation of effective strategies, as well as their ability to compete in the local and international markets. Sustainability in the context of halal fashion MSMEs involves several aspects, including the use of environmentally friendly materials, efficient management of natural and human resources, and attention to the social and economic welfare of workers. This study aims to analyze the development strategy of Sustainability-Based Halal Fashion Batik Style MSMEs. This study uses a qualitative motto by using the Nvivo application that supports searching for common words in data processing frequencies, displaying analysis in the form of tables and word frequencies that often appear based on the results of data coding. The results show that the words that appear most often are development, environment, society, growth, sustainable, meaning there is a relationship between these factors. The results of the study show that Langgam Batik develops its business based on three main pillars of sustainability, namely economic, social, and environmental. In terms of economy, product diversification and marketing with social media. From the social aspect, these MSMEs play a role in community empowerment through job creation and the preservation of cultural heritage through North Sumatran batik motifs. From an environmental perspective, there are opportunities to implement more environmentally friendly processes, such as the use of natural dyes that are less polluting. Therefore, support from the government, academics, and the business community is urgently needed to expand market reach and increase the competitiveness of halal fashion MSMEs at the national and international levels.